2019
DOI: 10.3390/medicina55060264
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Angiotensin-Converting Enzyme (ACE) Gene I/D Polymorphism with Preterm Birth in Korean Women: Case-Control Study and Meta-Analysis

Abstract: Background and Objectives: The ACE gene encodes the angiotensin-converting enzyme (ACE), a component of the renin-angiotensin system. Increased ACE activity may cause abnormal regulation of placental circulation and angiogenesis, resulting in adverse pregnancy outcomes. Previous studies have reported that the insertion/deletion (I/D) polymorphism of the ACE gene is associated with the development of preterm birth (PTB). However, results of the association between ACE gene I/D and PTB are inconsistent in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…25 In the current study, multivariate analysis showed birth weight, birth length, and head circumference did not interfere with the difference in the ACE gene polymorphism between the case and control group except for the gestational age, which was proposed by other studies to be associated with ACE gene polymorphism. 26,27 We concluded that in premature neonates, D/D genotype and D-alleles are protective factors from RDS. I/I genotype and I-alleles are associated with more severity and complications of RDS.…”
Section: Ras Activation May Influence Lung Injury By Modifying Vascul...mentioning
confidence: 89%
“…25 In the current study, multivariate analysis showed birth weight, birth length, and head circumference did not interfere with the difference in the ACE gene polymorphism between the case and control group except for the gestational age, which was proposed by other studies to be associated with ACE gene polymorphism. 26,27 We concluded that in premature neonates, D/D genotype and D-alleles are protective factors from RDS. I/I genotype and I-alleles are associated with more severity and complications of RDS.…”
Section: Ras Activation May Influence Lung Injury By Modifying Vascul...mentioning
confidence: 89%
“…A meta-analysis of 4 studies including 928 individuals (369 PTB cases and 559 controls) has revealed a significant association between ACE D allele carrier status and risk for PTB in various populations (58). On the contrary, another study in Korean women (111 PTB cases and 143 controls) have not observed such an association (62).…”
Section: The Ace I/d Polymorphism In Preterm Birthmentioning
confidence: 99%
“…PTB is caused by various factors, including abnormal placentation, inflammatory conditions, gestational bleeding, cervical and uterine abnormalities, as well as genetic factors (61,62). PTB has also been associated with blood pressure dysregulation during pregnancy, involving RAS and ACE in particular, while some studies have specifically suggested involvement of the ACE I/D polymorphism (58,61,62).…”
Section: The Ace I/d Polymorphism In Preterm Birthmentioning
confidence: 99%
“…Angiotensin-converting enzyme, an indirect regulator of blood pressure, may involve insertion/deletion (ACE I/D) polymorphisms in PE [ 113 – 115 ]. Preterm birth is associated with an insertion/deletion of ACE polymorphisms [ 116 ]. However, these results may be based on ethnicity [ 116 ] as pregnant women in Brazil showed a correlation between ACE polymorphisms and PE [ 113 ].…”
Section: Genetic Appraisal Of Raasmentioning
confidence: 99%